1996
DOI: 10.1128/iai.64.1.332-342.1996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 20K fimbria, a new adhesin of septicemic and diarrhea-associated Escherichia coli strains, that belongs to a family of adhesins with N-acetyl-D-glucosamine recognition

Abstract: Bovine septicemic Escherichia coli 31A agglutinates bovine, rabbit, and human erythrocytes and adheres in vitro to the brush border of bovine or ovine intestinal epithelial cells and to the human colon carcinoma Caco-2 cell line. The adhesion and hemagglutination of E. coli 31A are mediated by a chromosome-encoded fimbrial adhesin serologically distinct from known fimbrial adhesins found in enterotoxigenic and septicemic bovine E. coli strains. By electron microscopy studies the fimbriae designated 20K were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 44 publications
(69 reference statements)
3
53
0
1
Order By: Relevance
“…Therefore, strains producing both the CNF1 toxin and the CS31A antigen represent a new example of association between bacterial clones and plasmidmediated virulence factors. The gene encoding the F17 structural subunit was not detected among CNF1-producing strains whereas F17 are usually detected on about 50% of CS31A-producing pathogenic E. coli isolated from calves [11]. In accordance with results previously described [16], we suggest that genes encoding CNF1 and F17 are not present together on the bacterial chromosome.…”
Section: Genetic Detection Of Adhesins and Toxin Genessupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, strains producing both the CNF1 toxin and the CS31A antigen represent a new example of association between bacterial clones and plasmidmediated virulence factors. The gene encoding the F17 structural subunit was not detected among CNF1-producing strains whereas F17 are usually detected on about 50% of CS31A-producing pathogenic E. coli isolated from calves [11]. In accordance with results previously described [16], we suggest that genes encoding CNF1 and F17 are not present together on the bacterial chromosome.…”
Section: Genetic Detection Of Adhesins and Toxin Genessupporting
confidence: 90%
“…In a previous report, we have demonstrated that bovine CNF2-producing E. coli were genetically associated with ¢mbriae belonging to the F17 family [10]. In contrast, these CNF2-positive E. coli did not express the a¢mbrial CS31A adhesin whereas F17 ¢mbriae were often associated with CS31A in bovine isolates [10,11]. The CS31A adhesin, ¢rst described on E. coli strains isolated from calves with septicemia or diarrhea, is closely related to K88 ¢brillae expressed by porcine ETEC and promotes adhesion to an N-acetylneuraminic acid-containing receptor present in human Int-407 cells [12^14].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We found that S. maltophilia and purified SMF-1 agglutinated mouse and hen erythrocytes in the presence of 1% D-mannose but did not agglutinate sheep, ox, horse, or human RBC, suggesting species-specific recognition. N-terminal amino acid sequence analysis of the major repeating subunit of SMF-1 displayed 60% similarity with the fimbrial adhesins family comprising K99, F17, 20K, and G fimbriae of E. coli pathogroups, and CupA of P. aeruginosa (Guinée et al, 1976;Rhen et al, 1986;Lintermans et al, 1988;Bertin et al, 1996;Klemm and Schembri 2000;Vallet et al, 2001). This suggests that this fimbrial family extends to other genetically distant nonenteric bacterial genera.…”
Section: Discussionmentioning
confidence: 93%
“…Purified SMF-1 agglutinated erythrocytes of several animal species and this activity was inhibited by anti-SMF-1 antibodies. The major fimbrial subunit produced by S. maltophilia , a polypeptide of 17 kDa, was found to be highly related to the family of fimbrial adhesins comprised by the G, F17, K99 and 20K fimbriae produced by several Escherichia coli pathogroups, and CupA of Pseudomonas aeruginosa (Guinée et al ., 1976;Rhen et al ., 1986;Lintermans et al ., 1988;Bertin et al ., 1996;Klemm and Schembri, 2000;Vallet et al ., 2001). This relatedness, the ability to agglutinate erythrocytes, and the presence of abundant fimbriae on adhering organisms suggest that the SMF-1 fimbriae may be important for the adhesiveness on abiotic and biotic surfaces, and probably to the pathobiology caused by this emerging pathogen.…”
Section: Introductionmentioning
confidence: 99%